Investigation of Microbial Quality of Milk and Milk Products and Isolations of Some Major Bacteria in the Central and Northwestern Zones of Tigray, Ethiopia - Dawit Gebremichael; Alem Tadesse; Fsahatsion Hailemariam; Birhane Hailay; Hagos Hadgu; Girmay Kalayu (Veterinary Medicine International)
Safety and quality of milk and milk products are an increasing concern worldwide. Milk and milk products are major causes of milk-borne diseases due to contamination with microorganisms resulting from a lack of standard milk handling procedures and hygienic practices. Thus, the study aims to investigate the microbial quality and safety of cow milk and milk products and isolate some bacteria in Tigray. Questionnaires were conducted to assess milk handling procedures and hygienic practices. Samples were collected from different sampling points in the summer and winter seasons. Laboratory analyses were conducted using microbiological methods. SPSS version 20 was used to analyze the results. The overall mean total bacterial counts were 4.94, 6.02, 6.58, and 6.23 log10 CFU/mL for milk samples collected directly from the udder, milk container, cafeteria, and yogurt, respectively. Total bacterial counts exhibited statistically significant differences (p<0.001) among different sampling points. The bacterial load in the winter season was significantly higher than in the summer season (p<0.04). Highly significant differences in coliform counts were observed (p<0.001) with mean values of 4.29, 5.49, 6.22, and 5.86 log10 CFU/mL for milk samples obtained directly from the udder, milk container, cafeteria, and yogurt, respectively. The averages of spore-forming and psychrotrophic counts were 4.13 and 5.40 log10 CFU/mL, respectively. Escherichia coli, Salmonella species, and Staphylococcus aureus exhibited significant variations at different sampling points. The isolation rates of Salmonella spp., E. coli, and S. aureus were 41.7%, 75%, and 95.8%, respectively. Total bacterial counts and psychrotrophic counts of the butter were 4.34 and 4.38 log10 CFU/g, respectively. Overall, the results indicate that milk and milk products had high levels of contamination because the bacterial loads were significantly higher than standard limits (5 log10 CFU/mL). Therefore, public education and awareness campaigns on good hygienic practices for dairy farmers and cafeteria owners are essential. Implementation of stringent food quality and safety standards, along with effective regulatory measures, is imperative to ensure safeguard consumer health.